LEGAL CERTAINTY FOR CONSUMERS IN GOOD FAITH DUE TO THE DEVELOPER COMPANY BEING DECLARED BANKRUPT - Hie, Hengky Himawan; Iryani, Dewi; Setiawan, Puguh Aji Hari (Awang Long Law Review, 2025)
The issue of legal certainty for consumers in good faith in buying and selling houses becomes even more important when the developer company is declared bankrupt. Consumers who have carried out their obligations, whether in the form of down payment, installments, and repayment, are often only positioned as concurrent creditors in the bankruptcy settlement process. This study uses normative juridical legal methods with a statutory approach and a conceptual approach. The source of research data was obtained through literature studies which include primary legal materials in the form of the 1945 Constitution of the Republic of Indonesia, the Civil Code, Law Number 8 of 1999 concerning Consumer Protection, Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations, as well as several Supreme Court decisions related to developer bankruptcy cases. Secondary legal materials are derived from books, legal journals, and the results of previous research. Data analysis is carried out by interpreting laws in a systematic, contextual, and comparative manner to obtain the right legal construction. The results of the study show that there is a legal disharmony between the Consumer Protection Law and the Bankruptcy Law. Consumers in good faith are often only placed as concurrent creditors so that they do not get optimal legal protection. In fact, Article 28H of the 1945 Constitution guarantees the right of everyone to live and live properly. Therefore, there is a need for legal reconstruction that places consumers as preferred creditors or given a special position in developer bankruptcy, in order to realize legal certainty, justice, and utility. The author recommends that regulatory reform be carried out through amendments to the Bankruptcy Law by accommodating the legal protection of consumers in good faith as a form of implementation of the principles of social justice.